Glutaric Aciduria Type I Diagnosis Case with Normal Glutaryl Carnitine and Urine Organic Acid Analysis - Ebru Canda; Havva Yazıcı; Esra Er; Cenk Eraslan; Yasemin Atik Altınok; Hepsen Mine Serin; Sara Habif; Gül Serdaroğlu; Sema Kalkan Uçar; Hüseyin Onay; Ferda Özkınay; Mahmut Çoker (Galenos Yayinevi, 2018)
Glutaric aciduria Type I (GA-I) is a rare inherited metabolic disease, deficiency of glutaryl-CoA dehydrogenase results in accumulation of the putatively neurotoxic metabolites glutaric and 3-hydroxyglutaric acid (GA, 3-OH-GA) in body tissues, particularly within the brain. Here we presented a 3-year-old girl with hypotonia and dystonia diagnosed with GA-I although the repeated analysis of the carnitine profile and organic acid analyses were normal. The patient has motor, mental retardation, hypotonia. Her weight standard deviation score (SDS) was -1.86 SDS, height SDS was -0.55 SDS, head circumference SDS was -1.01. The physical examination was normal except severe hypotonia. Spot blood carnitine profile, blood amino acid, urine organic acid, lactic acid and pyruvic acid were normal in repeated analysis. Dystonia and spastic tetraparesis developed on her follow-up. Cranial magnetic resonance imaging revealed bilateral cortical atrophy and bilateral striatal and caudate nucleus T2 flair hyperintensities. In GCDH gene analysis p.Y123C (c.368A>G)/p.L340F (c.368A>G) mutation was found. There was no history of encephalopathy. The patient treated with levodopa and trihexyphenidyl and lysine-restricted diet. In the presence of bilateral striatal involvement and cortical atrophy and dystonia, GA-I should be kept in mind. Blood carnitine profile and urine organic acid analyses may not be consistent. It is important to evaluate the cases for genetic investigation.